AMAZING UNIPA RACE: A SHARED CLASSROOM EXPERIENCE - Hertiki, Hertiki (JET ADI BUANA, 2017)
What makes learners shun speaking English in the classroom?Are they are shy, lack of confidence or afraid of making grammaticalmistakes? One of many ways to overcome this problem is by usingcooperative learning. In cooperative learning, the undergraduates areencouraged to work in small groups in order to create3-D miniaturemodels and finally gallery walk. In the Universitas PGRI Adi Buana(UNIPA), there is an activity named ―Amazing UNIPA Race‖. An activityencourages students to use verbal communication during Cross CulturalUnderstanding (CCU) class. Students work in small groups and must alsobe a team player. Amazing UNIPA Race promotes fun learning activityand students‘ creativity in creating 3-D miniature models. Therefore, thispaper is intended to share and provide an activity as a model wherestudents are motivated to speak and enjoy fun activities. This paper ispresented as a hands-on experience of the Amazing UNIPA Race to theparticipants who want to use it for their classroom teaching.